TRANSFER PRICING AND MULTINATIONAL CORPORATIONS: AN IN- DEPTH ANALYSIS OF TRANSFER PRICING POLICIES AND THEIR IMPACTON TAXATION IN INDONESIA - Hety Devita; Loso Judijanto; Renika Hasibuan; Dwi Koerniawati; Irwan Musriza Harahap (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This study comprehensively examines the intricate relationship between transfer pricing policies and their impact on taxation in Indonesia, concentrating on the context of multinational corporations (MNCs). The research offers an in-depth exploration of the legislative framework governing transfer pricing, shedding light on the compliance requirements imposed on MNCs and the prevalent transfer pricing methods in Indonesia. The study addresses the challenges MNCs encounter in meeting compliance standards, emphasizing the complexities of documentation and adherence to the arm's length principle. Furthermore, it investigates the broader implications of transfer pricing practices on tax revenue and economic development within the Indonesian context. By conducting a detailed literature review and analysis, the research provides valuable insights into the dynamic interplay between regulatory frameworks, corporate practices, and their impact on the fiscal landscape. In conclusion, the study offers forward- looking recommendations for future reforms to enhance the effectiveness of transfer pricing regulations and minimize the risks of tax avoidance. These recommendations, grounded in a thorough understanding of the current landscape, seek to fortify Indonesia's regulatory framework and foster collaboration between tax authorities and MNCs. The research contributes to the existing body of knowledge in international taxation and economic governance, serving as a valuable resource for scholars, policymakers, and practitioners navigating the intricate terrain of transfer pricing in Indonesia.